Influence Factors of Effective Communication of Health Officers on Patient Satisfaction - Ulfia Rizki; Mappeaty Nyorong; Deli Theo; Indah Anggraini (Jurnal Perilaku Kesehatan Terpadu, 2022)
Effective communication is communication that can lead to a shift in the attitudes of the parties concerned. Patient discontent with healthcare services will occur if communication is ineffective. A powerful rule of communication is the Reach aspect, which stands for Respect, Empathy, Audible, Clarity, and Humbleness. This study aims to analyse the factors of effective communication on outpatient satisfaction at Cut Meutia Hospital, North Aceh Regency, Aceh Province. This study was a quantitative with an analytical survey with a cross-sectional approach with a sample of 100 respondents who were outpatients at Cut Meutia Hospital. Data analysis used chi-square test and multiple logistic regression test. Of the 100 respondents, the results of the univariate analysis showed that on the Respect, Empathy, Audible, Clarity, and Humble dimensions, more respondents gave a Bad rating. Bivariate analysis showed that there was a significant relationship between the dimensions Respect (0.009 < 0.05), Empathy (0.003<0.05), Audible (0.000<0.05), Clarity (0.001<0.05), and Humble (0.000<0.005) with Patient Satisfaction. In multivariate analysis it was found that the variables Respect (p=0.006, OR=17.159), Empathy (p=0.008, OR=11.401), Audible (p=0.004, OR=11.500), Clarity (p=0.001, OR=6.355), Humble (p = 0.002, OR = 2,991), and the Respect factor was the most dominant which correlated with Patient Satisfaction (OR = 17,159). REACH has an impact on how well outpatients are treated, with the Respect variable at Cut Meutia Hospital in North Aceh Regency, Aceh Province, being the most important component. In order to offer patients with satisfaction, it is expected of all officers to be able to develop excellent communication skills.